Tectonic Structures of the Mangazeya Ore Cluster (Verkhoyansk Range, NE Asia). Issue 1 (December 2020) - Prokopiev, Andrei V.; Tretyakov, Felix F.; Vasiliev, Dmitry A.
Abstract: The Mangazeya ore cluster is located in the central part of the West Verkhoyansk sector of the Verkhoyansk fold-and-thrust belt, in the zone of junction of the Kuranakh anticlinorium and the Sartang synclinorium. High-tonnage Ag deposits and occurrences are concentrated here, which are thought to be associated with the zones of longitudinal strike-slip faults and bedding-plane thrusts. Structural studies were conducted in the dome and the eastern limb of the Endybal anticline, in the areas of the Nizhne-Endybalskoe, Verkhne-Endybalskoe, Bezymyannoe, Vertikalnoe, Sterzhnevoe, and Semenovskoe ore deposits. The Endybal asymmetric anticline 10-15 km wide and 60 km long, with a wide gentle dome is the major tectonic structure of the territory. The conducted structural and statistical analyses of tectonic structures in the study area allowed better understanding of their specific features and trends in development. Morphology of the fold structures indicates manifestation of concentric-type folding produced by bending of strata as a result of bedding-plane slipping. The same NS orientation of the cleavage and folds gives unanimous evidence for their genetic relationship and formation in the conditions of EW horizontal compression. It is established that the structural paragenesis represented by fractures, normal faults, and extension structures in the hinge zone of the concentric Endybal anticline, which determines the general tectonic pattern of the Mangazeya ore cluster and controls localization of ore bodies, was formed at the first deformation stage or in course of bedding-plane faulting and fold-and-thrust deformations rather than as a result of strike-slip motions. It is shown that strike-slip motions of the second deformation stage not only produced new structures but also inherited disturbances of the previous stage. It is found that normal faults in the study area formed synchronously with the fold-and-thrust structures. A similar orientation of the major faults and the strike-slip faults suggests that the regional faults have strike-slip kinematics. The occurrence of different types of tectonic deformation is controlled by rock lithology.